Adapt to not just survive but thrive: resilience strategies of five-star hotels at difficult times. Issue 9 (3rd June 2021) - Shi, Fangfang; Shi, Da; Weaver, David; Samaniego Chavez, Carla Estefania
Abstract : Purpose: This research aims to explore the strategies and tactics taken by five-star hotels to create and sustain competitiveness at difficult times, the role of innovation among the initiatives taken and the factors that influence managers' decision in selection of coping measures. Design/methodology/approach: The research was conducted in two stages. The first stage focused on textual analysis of online news reports on luxury hotels' coping strategies taken between 2013 and 2018. At the second stage, expert interviews were carried out with 25 managers of five-star hotels to obtain richer information of hotels' responsive measures. The qualitative data were analyzed by thematic analysis. Findings: The results revealed that five-star hotels in China made adjustment in physical resource management, human resource management, marketing mix, operation process and external relations to maintain competitiveness during difficult times. A model of hotel resilience was developed based on the findings. Innovation was imbedded in the responsive measures throughout these areas. Managers' selection of coping measures was affected by the hotel's organizational culture, location, brand image and competitors. Practical implications: The model of hotel resilience serves as a useful reference to plan and select strategies and tactics to respond to similar external challenges. Hotel managers are recommended to embrace a variety of innovations directed at both internal management and customer service during challenging times. Originality/value: To the best of the authors' knowledge, this study is the first empirical research that systematically examines the measures taken by hotels during critical times to maintain competitiveness, linking these to contemporary post-Fordist operational trends.